The effectiveness of forensic genealogy techniques in The united kingdom – an experimental assessment. Issue 1 (December 2019) - Thomson, Jim; Clayton, Tim; Cleary, John; Gleeson, Maurice; Kennett, Debbie; Leonard, Michelle; Rutherford, Donna
Abstract: The use of forensic genealogy techniques to identify Joseph James DeAngelo as the prime suspect in the Golden State Killer case in 2018 has opened up a new approach to investigation of cold cases. Since that breakthrough, these methods have been reportedly applied to more than 50 investigations. To date, all of these relate to investigations in the US, where the high uptake of "direct-to-consumer" (DTC) genetic testing by individuals conducting private ancestral research has provided the necessary publicly available data for successful forensic investigations. We have conducted a study to assess the likely effectiveness of forensic genealogy techniques if applied to investigations in the UK. Volunteers provided their own SNP array data, downloaded from a DTC provider of their choice. These data sets were anonymised and uploaded to the GEDmatch Genesis genealogy website, mimicking data sets from unsourced crime samples. A team of experienced genealogists then attempted to identify the donors of the anonymised data sets by identifying relatives on the database and triangulating to determine their shared family lineages which were further investigated using traditional resources (such as birth, marriage, death and census records). Four individuals out of a convenience sample of ten we correctly identified, at least to the level of one of a set of siblings.